Observations of Temporal Variations in the 5303 Å Emission Line During a Coronal Mass Ejection Without Any Associated Solar Flare - V. Muthu Priyal; R. Ramesh; Jagdev Singh; K. Sasikumar Raja (The Astrophysical Journal)
Reports using total solar eclipse data indicate that the 5303 Å emission line is a promising tool for observing the thermodynamic changes due to coronal mass ejections (CMEs) close to the Sun. The Visible Emission Line Coronagraph (VELC) on board ADITYA-L1, the recently launched first Indian space solar mission, has now provided an opportunity to regularly observe the solar corona in the 5303 Å emission line. We present the first long-duration temporal observations of activity associated with a flareless CME from an active region at the west limb of the Sun, with the VELC. The observations were in the sit-and-stare mode for ≈7 hr. Our analysis shows a steady increase in the intensity of the line by ≈57%, followed by a gradual decrease to the initial level. The width of the line also showed changes, but opposite to that in the intensity. The width slowly decreased from 0.97 ± 0.01 Å to 0.87 ± 0.01 Å and then increased back. The change is ≈10%. The effective temperatures corresponding to each of the above two widths are 3.39 ± 0.1 × 10 ^6 K and 2.74 ± 0.1 × 10 ^6 K, respectively. The Doppler velocity changed gradually from 0 ± 0.5 km s ^−1 to −3 ± 0.5 km s ^−1 during the abovementioned intensity increase phase. It slowly reverted to 0 ± 0.5 km s ^−1 when the intensity decreased.